ChemInform Abstract: Towards the Rational Design of Efficient Organic Structure‐Directing Agents for Zeolite Synthesis. Issue 12 (25th March 2014) - Moliner, Manuel; Rey, Fernando; Corma, Avelino
Abstract Review: 78 refs.